MODALITY IN GIVING ADVICE IN AN INDONESIAN EFL TEXTBOOK: INSIGHTS FROM SYSTEMIC FUNCTIONAL LINGUISTICS - Siburian, Irene Nataly; Yogi Setia Samsi; Kelik Wachyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Modality plays an important role in expressing interpersonal meaning, particularly in giving advice within English language teaching materials. This study investigates the realization of modality in giving advice in the Indonesian EFL textbook Interactive English 2 and explores its pedagogical implications. The study employed a qualitative document analysis. The research corpus consisted of clauses realizing giving advice, identified from Unit 1 of the textbook after all instructional units had been systematically screened. The findings revealed that giving advice was predominantly realized through the modal operators should and shouldn't. The analysis showed that